Social Inclusion by Revitalisation? The Potential of Disused Industrial Areas as an Opportunity for Mitigating Social Polarisation - Otto, Marius; Chmielewska, Marta (Quaestiones Geographicae, 2014)
The paper concerns the relation between revitalisation projects and socio-economic polarisation, and discusses the potential of new urban spaces for social inclusion. The phenomenon is considered on the example of recreational facilities that have emerged from brownfields located in the Ruhr region (Germany). It was ascertained that the diversity of implemented projects was important in terms of the significance of revitalisation processes for social polarisation tendencies. It allowed regional authorities to create income-generating facilities and spaces that can be used regardless of income, and to resolve deficits in urban recreational facilities. It was also noted that the Ruhr examples could provide guidance for the recently begun revitalisation processes in the Upper Silesian industrial area (Poland).